Superstar returns - Francisco Osswald do Amaral; Martin Dohmen; Sebastian Kohl; Moritz Schularick (University of Bonn and University of Cologne, Reinhard Selten Institute (RSI), 2021)
We study long-term returns on residential real estate in 27 "superstar" cities in 15 countries over 150 years. We find that total returns in superstar cities are close to 100 basis points lower per year than in the rest of the country. House prices tend to grow faster in the superstars, but rent returns are substantially greater outside the big agglomerations, resulting in higher long-run total returns. The excess returns outside the superstars can be rationalized as a compensation for risk, especially for higher co-variance with income growth and lower liquidity. Superstar real estate is comparatively safe.
Keywords: G10; G12; N90; R21; R31; 330; housing returns; housing risk; superstar cities; regional housing markets